HOLISTICS JOURNAL HOLISTICS JOURNAL HOSPITALITY AND LINGUISTICS: The Influence of English Mastery toward the Public Speaking Skills in English Department at State Polytechnic of Sriwijaya - Zakaria Zakaria; Darmaliana Darmaliana; Eli Yeny (Politeknik Negeri Sriwijaya, 2021)
The purpose of this research is to know whether there is the influence of English mastery toward the public speaking skill in English Department at State Polytechnic of Sriwijaya or not. This research is ex post facto design with quantitative data approach. The subject of this research is 6th semester of English Department. Documentation and test used to collect the data in this research. The data validity uses Simple Linear Regression Analysis with prerequisite analysis test consisted of data normality test, data linearity test, and hypothesis test. The result of this research is there is no influence between English mastery toward the public speaking skill. This is shown from the results of a simple regression analysis where the value of sig. of 0.789 > 0.05. The influence is only 0.004 or 0.004 x 100% = 0.4%, which means that the influence between the two variables is very small. And the remaining 99.6% is influenced by other variables not examined.